Formation of non-substitutional beta-Sn defects in Ge1-x Snx alloys - Fuhr, Javier Daniel (2013)
Although group IV semiconductor alloys are expected to form substitutionally, in Ge1xSnx this is true only for low concentrations (x < 0.13). The use of these alloys as a narrow gap semiconductor depends on the ability to produce samples with the high quality required for optoelectronic device applications. In a previous paper, we proposed the existence of a non-substitutional complex defect (b-Sn), consisting of a single Sn atom in the center of a Ge divacancy, which may account for the segregation of Sn at large x. Afterwards, the existence of this defect was confirmed experimentally. In this paper we study the local environment and the interactions of the substitutional defect (a-Sn), the vacancy in Ge, and the b-Sn defect by performing extensive numerical ab initio calculations. Our results confirm that a b-Sn defect can be formed by natural diffusion of a vacancy around the substitutional a-Sn defect, since the energy barrier for the process is very small.